Decoration of Vertically Aligned Carbon Nanotubes with Semiconductor Nanoparticles Using Atomic Layer Deposition - Szabó, Anna (Materials (Basel), 2019)
Vertically aligned carbon nanotubes (VACNTs or “CNT forest”) were decorated with semiconductor particles (TiO(2) and ZnO) by atomic layer deposition (ALD). Both the structure and morphology of the components were systematically studied using scanning (SEM) and high resolution transmission electron microscopy (HRTEM), energy-dispersive X-ray spectroscopy (EDX), Raman spectroscopy, and X-ray diffraction (XRD) methods. Characterization results revealed that the decoration was successful in the whole bulk of VACNTs. The effect of a follow-up heat treatment was also investigated and its effect on the structure was proved. It was attested that atomic layer deposition is a suitable technique for the fabrication of semiconductor/vertically aligned carbon nanotubes composites. Regarding their technological importance, we hope that semiconductor/CNT forest nanocomposites find potential application in the near future.